(untitled) (Progressive Agriculture, 2014)
This study was conducted to evaluate the effect of carboxymethyl cellulose (CMC) and starch used as thickening agents on physicochemical properties of tomato juice. The pulp was extracted from ripe and sound tomatoes and subsequently used for preparation of tomato juice with the addition of different levels of starch and CMC including other ingredients. The CMC was used at the rate of 0.1-0.3% while starch was 0.3 -1% in the prepared juice. The moisture content of juice was increased adding of both the thickening agents. The ash content and acidity of tomato juice were decreased gradually with the increasing level of starch and CMC. The highest ash content and acidity were found in juice without added starch and CMC. The lowest ash and acid content was found in the juice incorporated with 1% and 0.3% starch and CMC respectively. Ascorbic acid was decreased with the increase of both thickening agents. The prepared juice was remained unchanged within two months. After two months, colour and flavour were changed and various bacterial load was increased. DOI: http://dx.doi.org/10.3329/pa.v18i2.18245 Progress. Agric. 18(2): 235 - 240, 2007